Office Management of Dyslipidemia - Gary Tabas; James McGee; Peter Kant (Association of American Medical Colleges, 2010)
Abstract Introduction This educational module is intended for medical students in their clinical years, and internal medicine and family practice residents in any year. Its purpose is to teach the evaluation and management of commonly encountered dyslipidemic syndromes using the Adult Treatment Panel III of the National Cholesterol Education Program guidelines. Methods Each section of the module begins with a case vignette followed by a multiple-choice question (MCQ) based on the case. Answers follow each MCQ. A brief text page with bulleted points that further explain the teaching points follows each MCQ. The text page has links to supporting tables and online tools. The length of the text pages is limited in order to avoid cognitive overload. The module ends with a scored posttest consisting of 10 MCQ's with answers. Results The effectiveness of the Office Management of Dyslipidemia module was tested by assessing internal medicine residents' ability to pass the posttest. Results showed that 63% of residents passed the posttest on the first attempt and 23% and 2% passed on the second and third attempts respectively. Seven percent did not pass after three attempts and 5% did not complete the posttest. Discussion In the Adult and Family Nurse Practitioner Program at the University of Pittsburgh, modules were used in the Acute and Chronic courses. The instructors added module content to their courses and felt that students did well with MCQs in the modules. The significance of using an educational module to teach the management of dyslipidemia is that the module learning allows standardization of the didactic materials. The module incorporates adult learning theory including active learning, problem solving and self-evaluation.